A TiO2 grafted bamboo derivative nanocellulose polyvinylidene fluoride (PVDF) nanocomposite membrane for wastewater treatment by a photocatalytic process - Md Rezaur, Rahman; Anthonette, James; Khairul Anwar, Mohamad Said; Murtala, Namakka; Mayeen Uddin, Khandaker; Woo, Haw Jiunn; Jehan Y., Al-Humaidi; Raed H., Althomali; Mohammed Muzibur, Rahman (The Royal Society of Chemistry, 2024)
The escalating demands for efficient wastewater treatment drive this study, which explores the development and characterization of polyvinylidene fluoride (PVDF) nanocomposite membranes enhanced with nanocellulose (NC) and titanium dioxide (TiO2). The integration of NC and TiO2 nanoparticles into a PVDF matrix via the phase inversion method yielded notable improvements in the structural, mechanical, and functional properties of the membranes. Fourier-transform infrared spectroscopy (FTIR) analysis confirmed the presence of critical functional groups that facilitated improved interactions within the nanocomposite membrane. These interactions contributed to the enhanced membrane hydrophilicity, suggesting their potential to improve water permeability. Field emission scanning electron microscopy (FESEM) revealed the uniform dispersion of TiO2 and NC at optimal loadings, which minimized nanoparticle agglomeration and promoted the formation of a more porous and permeable membrane structure. X-ray diffraction (XRD) showed an increase in the crystallinity of the β-phase of PVDF, thus enhancing mechanical stability and overall membrane functionality. The optimization of TiO2 loading at 3 wt% resulted in maximum efficacy, with a 15% increment in water flux rates from 234.06 L m−2 h−1 to 270.23 L m−2 h−1 over an unmodified PVDF/NC membrane and achieving methylene blue (MB) dye rejection rates of up to 98%. The enhanced physical properties of the membrane, resulting from a reduction in mean pore size from 0.00488 to 0.00470 µm and improved porosity from 76.07% to 79.68% ensured more effective filtration. These modifications have surpassed the performance of the unmodified PVDF/NC membrane. Additionally, the presence of TiO2 nanoparticles significantly enhanced the photocatalytic properties of the membranes, accelerating the degradation of MB pollutants and improving antifouling properties. This was evidenced by the high flux recovery rate (FRR) percentage, which underscores their superior self-cleaning capabilities. These findings illustrate that the synergistic integration of NC and TiO2 not only capitalized on the individual properties of each component but also significantly elevated overall membrane performance and maintained longevity in their practical usage. This study represents a significant advancement in membrane technology, offering new avenues for sustainable and efficient environmental remediation and presenting robust solutions to challenges such as membrane fouling.